Optimal. Leaf size=17 \[ -\frac {7 (\log (-1-x)+\log (x))}{e^2 x} \]
________________________________________________________________________________________
Rubi [A] time = 0.41, antiderivative size = 25, normalized size of antiderivative = 1.47, number of steps used = 15, number of rules used = 10, integrand size = 38, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.263, Rules used = {12, 1593, 6741, 6742, 77, 2395, 36, 31, 29, 2304} \begin {gather*} -\frac {7 \log (-x-1)}{e^2 x}-\frac {7 \log (x)}{e^2 x} \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
Rule 12
Rule 29
Rule 31
Rule 36
Rule 77
Rule 1593
Rule 2304
Rule 2395
Rule 6741
Rule 6742
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\frac {\int \frac {-7-14 x+(7+7 x) \log (-1-x)+(7+7 x) \log (x)}{x^2+x^3} \, dx}{e^2}\\ &=\frac {\int \frac {-7-14 x+(7+7 x) \log (-1-x)+(7+7 x) \log (x)}{x^2 (1+x)} \, dx}{e^2}\\ &=\frac {\int \frac {7 (-1-2 x+\log (-1-x)+x \log (-1-x)+\log (x)+x \log (x))}{x^2 (1+x)} \, dx}{e^2}\\ &=\frac {7 \int \frac {-1-2 x+\log (-1-x)+x \log (-1-x)+\log (x)+x \log (x)}{x^2 (1+x)} \, dx}{e^2}\\ &=\frac {7 \int \left (\frac {-1-2 x+\log (-1-x)+x \log (-1-x)}{x^2 (1+x)}+\frac {\log (x)}{x^2}\right ) \, dx}{e^2}\\ &=\frac {7 \int \frac {-1-2 x+\log (-1-x)+x \log (-1-x)}{x^2 (1+x)} \, dx}{e^2}+\frac {7 \int \frac {\log (x)}{x^2} \, dx}{e^2}\\ &=-\frac {7}{e^2 x}-\frac {7 \log (x)}{e^2 x}+\frac {7 \int \left (\frac {-1-2 x}{x^2 (1+x)}+\frac {\log (-1-x)}{x^2}\right ) \, dx}{e^2}\\ &=-\frac {7}{e^2 x}-\frac {7 \log (x)}{e^2 x}+\frac {7 \int \frac {-1-2 x}{x^2 (1+x)} \, dx}{e^2}+\frac {7 \int \frac {\log (-1-x)}{x^2} \, dx}{e^2}\\ &=-\frac {7}{e^2 x}-\frac {7 \log (-1-x)}{e^2 x}-\frac {7 \log (x)}{e^2 x}-\frac {7 \int \frac {1}{(-1-x) x} \, dx}{e^2}+\frac {7 \int \left (-\frac {1}{x^2}-\frac {1}{x}+\frac {1}{1+x}\right ) \, dx}{e^2}\\ &=-\frac {7 \log (-1-x)}{e^2 x}-\frac {7 \log (x)}{e^2}-\frac {7 \log (x)}{e^2 x}+\frac {7 \log (1+x)}{e^2}+\frac {7 \int \frac {1}{-1-x} \, dx}{e^2}+\frac {7 \int \frac {1}{x} \, dx}{e^2}\\ &=-\frac {7 \log (-1-x)}{e^2 x}-\frac {7 \log (x)}{e^2 x}\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.04, size = 24, normalized size = 1.41 \begin {gather*} \frac {7 \left (-\frac {\log (-1-x)}{x}-\frac {\log (x)}{x}\right )}{e^2} \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.51, size = 16, normalized size = 0.94 \begin {gather*} -\frac {7 \, {\left (\log \relax (x) + \log \left (-x - 1\right )\right )} e^{\left (-2\right )}}{x} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [A] time = 0.16, size = 21, normalized size = 1.24 \begin {gather*} -7 \, {\left (\frac {\log \relax (x)}{x} + \frac {\log \left (-x - 1\right )}{x}\right )} e^{\left (-2\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.46, size = 24, normalized size = 1.41
method | result | size |
risch | \(-\frac {7 \,{\mathrm e}^{-2} \ln \left (-x -1\right )}{x}-\frac {7 \,{\mathrm e}^{-2} \ln \relax (x )}{x}\) | \(24\) |
default | \({\mathrm e}^{-2} \left (7 \ln \left (-x \right )+\frac {7 \ln \left (-x -1\right ) \left (-x -1\right )}{x}-\frac {7 \ln \relax (x )}{x}-7 \ln \relax (x )+7 \ln \left (x +1\right )\right )\) | \(46\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [B] time = 0.40, size = 41, normalized size = 2.41 \begin {gather*} -7 \, {\left (\frac {{\left (x + 1\right )} \log \relax (x) - {\left (x - 1\right )} \log \left (-x - 1\right ) + 1}{x} - \frac {1}{x} + \log \left (x + 1\right ) - \log \relax (x)\right )} e^{\left (-2\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 7.23, size = 16, normalized size = 0.94 \begin {gather*} -\frac {7\,{\mathrm {e}}^{-2}\,\left (\ln \left (-x-1\right )+\ln \relax (x)\right )}{x} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.42, size = 24, normalized size = 1.41 \begin {gather*} - \frac {7 \log {\relax (x )}}{x e^{2}} - \frac {7 \log {\left (- x - 1 \right )}}{x e^{2}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________